ERROR ANALYSIS OF SIMPLE PRESENT IN WRITING DESCRIPTIVE TEXT - Indah Lestari (Journal of English Language Teaching and English Linguistics, 2020)
The purpose of this study was to determine the extent of the ability to write descriptive text. This research was conducted at the University of PGRI Yogyakarta and specifically investigated how simple present tense is used and which errors are most often done by research subjects.The subjects of this study were 8 4th-semester students majoring in English Education at PGRI University of Yogyakarta. Researcher used qualitative descriptive method in this study. The first step taken by researcher was to gave students three themes, namely Family, My Idol & Beautiful Place in Yogyakarta. After that students choose one of these themes and then wrote it into descriptive text. By using the Surface Strategy Taxonomy, researcher then classify what errors they have made.The results of this study indicate that students made 33 errors (47.14%) from 70 Present Present Tense sentences. This was less than the correct use of Simple Present Tense, with a total of 37 (52.86%). Students made the most error in misformation by 13 (39.39%). Whereas the most rarely made error is addition with a total of 2 (6.07%).